Genetic characterization of clinical Klebsiella isolates circulating in Novosibirsk - A. V. Bardasheva; N. V. Fomenko; T. V. Kalymbetova; I. V. Babkin; S. O. Chretien; E. V. Zhirakovskaya; N. V. Tikunova; V. V. Morozova (Вавиловский журнал генетики и селекции)
72 clinical strains of Klebsiella spp. isolated from samples obtained from humans in Novosibirsk, Russia, were analyzed. Species identification of strains was performed using 16S rRNA and rpoB gene sequences. It was revealed that Klebsiella pneumoniae strains were dominant in the population (57 strains), while the remaining 15 strains were K. grimontii, K. aerogenes, K. oxytoca and K. quasipneumoniae. By molecular serotyping using the wzi gene sequence, K. pneumoniae strains were assigned to twenty-one K-serotypes with a high proportion of virulent K1- and K2-serotypes. It was found that K. pneumoniae strains isolated from the hospitalized patients had a higher resistance to antibiotics compared to the other Klebsiella species. Real-time PCR revealed that the population contained genes of the blaSHV, blaTEM, blaCTX families and the blaOXA-48 gene, which are the genetic determinants of beta-lactam resistance. It has been shown that the presence of the blaCTX sequence correlated with the production of extended-spectrum beta-lactamases, and phenotypic resistance to car-bapenems is due to the presence of the blaOXA-48 gene. At the same time, the carbapenemase genes vim, ndm, kpc, imp were not detected. Among the aminoglycoside resistance genes studied, the aph(6)-Id and aadA genes were found, but their presence did not always coincide with phenotypic resistance. Resistance to fluoroquinolones in the vast majority of strains was accompanied by the presence of the aac(6’)-IB-cr, oqxA, oqxB, qnrB, and qnrS genes in various combinations, while the presence of the oqxA and/or oqxB genes alone did not correlate with resistance to fluoroquinolones. Thus, the detection of blaCTX and blaOXA-48 can be used to quickly predict the production of extended-spectrum beta-lactamases and to determine the resistance of Klebsiella to carbapenems. The detection of the aac(6’)-Ib-cr and/or qnrB/qnrS genes can be used to quickly determine resistance to fluoroquinolones.